2018
DOI: 10.1017/s0263574718001200
|View full text |Cite
|
Sign up to set email alerts
|

Smart Navigation of Humanoid Robots Using DAYKUN-BIP Virtual Target Displacement and Petri-Net Strategy

Abstract: SummaryWith an ability to mimic the human behaviour and replace human efforts in proper platforms, humanoid robots have always acquired a special place among robotics practitioners. Being a complex method of analysis, navigation and path planning, humanoid robots still possess an interesting yet challenging area of investigation. In the current work, a novel navigational strategy has been proposed for smooth and hassle-free movement of single as well as multi-humanoid robots in complex environments. Here, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Therefore, it is necessary to revise the production line plan. Through analysis, it is found that the reason for the bad posture is due to the low height of the storage point and the machine tool [ 23 , 24 ]. Taking into account the actual production situation, the physical height of the storage point and station 1 can be increased by 50 cm and the OWAS report and BSHA report as shown in Figure 2 can be obtained.…”
Section: Results Analysismentioning
confidence: 99%
“…Therefore, it is necessary to revise the production line plan. Through analysis, it is found that the reason for the bad posture is due to the low height of the storage point and the machine tool [ 23 , 24 ]. Taking into account the actual production situation, the physical height of the storage point and station 1 can be increased by 50 cm and the OWAS report and BSHA report as shown in Figure 2 can be obtained.…”
Section: Results Analysismentioning
confidence: 99%
“…e small hole imaging model of the camera [10] is an ideal camera model. It is impossible for the actual lens to maintain such an ideal state during the manufacturing process, which causes the deformation of the actual object in the imaging plane.…”
Section: E Distortion Model Of the Cameramentioning
confidence: 99%
“…Differential evolution algorithm [69] has been used by the researchers to address many optimisation problems. Daykun-bip [70] AI technique is a smart computational method, used by researchers to address path planning of robots in unknown environments.…”
Section: Introductionmentioning
confidence: 99%